Spatial scale changes the relationship between beta diversity, species richness and latitude. Issue 9 (19th September 2018) - Sreekar, Rachakonda; Katabuchi, Masatoshi; Nakamura, Akihiro; Corlett, Richard T.; Slik, J. W. Ferry; Fletcher, Christine; He, Fangliang; Weiblen, George D.; Shen, Guochun; Xu, Han; Sun, I-Fang; Cao, Ke; et al.
Abstract : The relationship between β-diversity and latitude still remains to be a core question in ecology because of the lack of consensus between studies. One hypothesis for the lack of consensus between studies is that spatial scale changes the relationship between latitude and β-diversity. Here, we test this hypothesis using tree data from 15 large-scale forest plots (greater than or equal to 15 ha, diameter at breast height ≥ 1 cm) across a latitudinal gradient (3–30 o ) in the Asia-Pacific region. We found that the observed β-diversity decreased with increasing latitude when sampling local tree communities at small spatial scale (grain size ≤0.1 ha), but the observed β-diversity did not change with latitude when sampling at large spatial scales (greater than or equal to 0.25 ha). Differences in latitudinal β-diversity gradients across spatial scales were caused by pooled species richness (γ-diversity), which influenced observed β-diversity values at small spatial scales, but not at large spatial scales. Therefore, spatial scale changes the relationship between β-diversity, γ-diversity and latitude, and improving sample representativeness avoids the γ-dependence of β-diversity.